Validation of the Korean version of the thyroid cancer-specific quality of life questionnaire - Jeong, Youjin (Ann Surg Treat Res, 2015)
PURPOSE: The increasing incidence of thyroid cancer worldwide has drawn attention to the needs for assessing and managing health-related quality of life (HRQoL) of thyroid cancer survivors. We conducted this study to validate the Korean version of the thyroid cancer-specific quality of life (THYCA-QoL) questionnaire. METHODS: Data obtained from 227 thyroid cancer survivors were analyzed using standard validity and reliability analysis techniques. Reliability was assessed by measuring internal consistency via Cronbach α coefficient, and validity was assessed by determining the Pearson correlation coefficient between the THYCA-QoL questionnaire and the following relevant assessment tools: the European Organization for Research and Treatment of Cancer QLQ-C30 (EORTC QLQ-C30), the Korean version of Brief Fatigue Inventory (BFI-K), the Korean version of Brief Encounter Psychosocial Instrument (BEPSI-K), Goldberg Short Screening Scale for Anxiety and Depression, and a nine-item Patient Health Questionnaire (PHQ-9). A multitrait scaling analysis was performed to assess each item's convergent and discriminant validity. RESULTS: The reliability of the THYCA-QoL questionnaire was confirmed by Cronbach α coefficients for multiple-item scales which ranged from 0.54 (sensory) to 0.82 (psychological). Except for a single item (sexual interest), the questionnaire's validity was established by significant correlation observed between scales in the THYCA-QoL questionnaire and scales used in other assessment tools. A multitrait scaling analysis confirmed that all scales met the recommended psychometric standards. CONCLUSION: The Korean version of the THYCA-QoL questionnaire is a reliable and valid assessment tool that can be used in combination with the EORTC QLQ-C30 to assess the HRQoL of thyroid cancer survivors in Korea.